2023 Methods-of-Payment Survey report: The resilience of cash - Christopher Henry; Matthew Shimoda; Doina Rusu (Bank of Canada, 2024)
We present key results from the 2023 Methods-of-Payment (MOP) Survey, including updated payment shares based on a three-day shopping diary. Results show that measures of cash management and use have remained fairly stable since 2020, along with the estimated share of payments made online. In 2023, Canadians increased their adoption of payment alternatives such as mobile apps and Interac e-Transfer. New questions were introduced into the MOP survey instrument in 2023 to measure perceived access to cash from automated banking machines and banks.
Keywords: D83; E41; 330; Bank notes; Digital currencies and fintech; Financial services